### Solved Example 1

Expand the expression `(x + 2y)^3`

### Solution

Compare the given expression with `(a + b)^3`. Thus,

Write the formula,`a = x` and `b = 2y`

`(a + b)^3 = a^3 + b^3 + 3ab(a + b)`Put 'x' in place of 'a' and '2y' in place of 'b',

`(x + 2y)^3 = x^3 + (2y)^3 + 3(x)(2y)(x + 2y)`Simplify the expression,

`(x + 2y)^3 = x^3 + 8y^3 + 6x^2y + 12xy^2`

### Solved Example 2

Expand the expression `(3a + 4b)^3`

### Solution

Compare the given expression with `(a + b)^3`. Thus,

Write the formula,`a = 3a` and `b = 4b`

`(a + b)^3 = a^3 + b^3 + 3ab(a + b)`Put '3a' in place of 'a' and '4b' in place of 'b',

`(3a + 4b)^3 = (3a)^3 + (4b)^3 + 3(3a)(4b)(3a + 4b)`Simplify the expression,

`(3a + 4b)^3 = 27a^3 + 64b^3 + 36ab(3a + 4b)`

`= 27a^3 + 64b^3 + 108a^2b + 144ab^2`

### Solved Example 3

Expand the expression `(x + y/2)^3`

### Solution

Compare the given expression with `(a + b)^3`. Thus,

Write the formula,`a = x` and `b = y/2`

`(a + b)^3 = a^3 + b^3 + 3ab(a + b)`Put `x` in place of 'a' and `y/2` in place of 'b',

`(x + y/2)^3 = (x)^3 + (y/2)^3 + 3(x)(y/2)(x + y/2)`Simplify the expression,

`(x + y/2)^3 = x^3 + (y^3)/8 + (3xy)/2(x + y/2)`

`= x^3 + (y^3)/8 + (3x^2y)/2 + (3xy^2)/4`

### Solved Example 4

Expand the expression `(x/3 + y/4)^3`

### Solution

Compare the given expression with `(a + b)^3`. Thus,

Write the formula,`a = x/3` and `b = y/4`

`(a + b)^3 = a^3 + b^3 + 3ab(a + b)`Put `x/3` in place of 'a' and `y/4` in place of 'b',

`(x + y/2)^3 = (x)^3 + (y/2)^3 + 3(x)(y/2)(x + y/2)`Simplify the expression,

`(x + y/2)^3 = x^3 + (y^3)/8 + (3xy)/2(x + y/2)`

`= x^3 + (y^3)/8 + (3x^2y)/2 + (3xy^2)/4`

## No comments:

## Post a Comment